Effects of persulfate and hydrogen peroxide on oxidation of oxalate by pulsed corona discharge; Chemical Engineering Journal; Vol. 411 - Tikker P. Priit; Dulova N. Niina; Kornev Ya. I. Yakov Ivanovich; Preys S. Sergey (2021, 2021)
Title screen